THE ANALYSIS OF KERIS FROM AUTHORITY AND WORLD CULTURAL BEHAVIOR - Addiina Purnawangsih; Slamet Subiyantoro; Edy Tri Sulistyo (Proceeding of International Conference on Art, Language, and Culture, 2017)
The objective of the study is to describe Keris from the point of view of cultural elements. This research is anthropological by analyzing art branch of art that is Keris, where its position is culture, which has seven cultural element. Technique of collecting data with observation, interview and analysis of document / archive contents. Stages of analysis is done by collecting data, data reduction, data presentation and verification. The study concluded that Keris has religious meaning, source of livelihood, social organization, local knowledge, language, artistry and technological meaning. All elements of culture inherent in the keris possess each form of ideas, social behavior and physical form.